PENERAPAN TERAPI LATIHAN KETRAMPILAN SOSIAL PADA KLIEN ISOLASI SOSIAL DAN HARGA DIRI RENDAH DENGAN PENDEKATAN MODEL HUBUNGAN INTERPERSONAL PEPLAU DI RS DR MARZOEKI MAHDI BOGOR - Abdul Wakhid; Achir Yani S. Hamid; Novy Helena CD (Universitas Muhammadiyah Semarang, 2013)
Application of social skills training therapy to client with social isolation and low self esteem disturbance with Interpersonal relationship Peplau Model Approach in RS Dr Marzoeki Mahdi Bogor. Social skills training was designed to improve communication and social skills for someone was experienced difficulties in their interaction skills include giving reinforcement, complain because they do not agree, reject the request of other, exchange experience, demanding personal rights, give advice to others, problem solving and working with people, sharing experience, ask for privacy (Michelson, 1985). Objective this final assignment was to founddescribing result of Application of social skills training therapy management on Social isolation and low self esteem client with interpersonal relationship Peplau Model approach in RS Dr Marzoeki Mahdi Bogor. Application of social skills therapy was done to 18 clients since 10 September-9 November 2012. Finding was revealed social skills training exactly effective may used for client with social isolation and low self esteem, where all of clients who have done social skills therapy. Base on this finding, recommended social skills training become to specialist standard therapy in psychiatric nursing and may used for social isolation and low self esteem clients. Key word : social skills training, social isolation, low self esteem, Peplau interpersonal model